Communication Patterns of the Learning and Training Process in the Hypehope Bali Dance Community - Suparna, Putu; Arta, Kadek Ananda Dwi Febri (Journal Corner of Education, Linguistics, and Literature, 2025)
This study analyzes communication patterns within the Hypehope Bali community, a dance organization that emphasizes coordination between leaders, mentors, and students. The research aims to identify and understand the application of wheel communication patterns, formal and informal interactions, and socialization mechanisms that support the community's operational efficiency. Using field observation and in-depth interviews, the study reveals that the wheel communication pattern is implemented with the leader as the central decision-maker, who conveys information to mentors and subsequently to students. Formal communication is applied in contexts requiring clarity, such as meetings and technical instructions, while informal communication dominates daily interactions to foster familiarity and strengthen relationships among members. Additionally, socialization mechanisms introduce the community’s values and culture to new members through internal media such as WhatsApp groups and meetings, as well as external social media platforms. The findings indicate that Hypehope Bali’s success in creating a harmonious and productive environment heavily relies on the integration of various communication patterns. This study recommends continuous monitoring of communication processes to address the challenges of new member adaptation and enhance coordination efficiency within the community.